Dose Rate Calibration of β Radiation Source in Risø TL/OSL-DA-20 Reader Device - Avcı, Hamide; Bulcar, Kenan; Oğlakçı, Mehmet; Atav, Ülfet (International Journal of Computational and Experimental Science and Engineering, 2024)
This research is focused on determining the dose rate calibration of beta irradiation source in the Risø brand TL/OSL-DA-20 model thermoluminescence (TL) and optically stimulated luminescence (OSL) reader device manufactured by DTU Physics which is an integral component of the Technical University of Denmark (DTU). The beta radiation source of this device comprises a pellet-shaped Strontium ceramic made from the 90Sr/90Y radionuclide, with a half-life of approximately 29.1 years. This investigation provides a thorough examination of reproducing equivalent dose levels by comparing reproduced OSL signals with the OSL signals of calibration quartz crystals which were previously exposed to a 5 Gy beta radiation emission. Throughout this process, dose durations and equivalent dose levels were analysed on optically stimulated luminescence signals. The collected OSL data aims to ensure the precise calibration of the radioactive source, contributing to reliable results in dosimetric measurements. This calibrated device is utilized in the Luminescence Laboratory co-run by the Physics Department and Nuclear Materials Research and Application Center of Selçuk University. The determined dose rate of the beta radiation source is found as 0.065 Gy/second.